THE INFLUENCE OF SLANG IN UNDERSTANDING THE MESSAGE OF DA'WAH AMONG THE MILLENNIAL GENERATION - Ningtyas, Baqiya Aini Wahyu; Muslim, Sukma Bangkit Panji; Aulia, Novia Rahma; Solihati, Ade Titie; Sunarya, Fitri Rachmiati (Journal of Islamic Studies, 2024)
This study examines the influence of slang in the understanding of da'wah messages among millennials. Slang affects millennials' responsiveness to da'wah messages with a tendency for better understanding when delivered in familiar language. Social and cultural contexts also influence the understanding of da'wah messages with millennials being more open to messages that are inclusive and relevant to their lives. The digital-savvy characteristics of millennials also play a role in how they receive and disseminate da'wah messages. This understanding can help da'wah activists deliver religious messages effectively to millennials. Further studies are needed to explore the impact of slang in the context of da'wah and strengthen the understanding of millennials in the religious realm